PENGARUH SOSIALISASI DAN PEMAHAMAN KEBIJAKAN SUNSET POLICY TERHADAP KEMAUAN MEMBAYAR PAJAK (Studi Kasus Pada Wajib Pajak Badan di KPP Pratama Surakarta) - Dewi Saptantinah Puji Astuti, Astride Dian Puspita, Fadjar Harimurti & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The objectives of the study are to analyze the influence of (1) the dissemination of Sunset Policy toward the willingness of paying tax; (2) the comprehension of tax payers toward Sunset policy on the willingness of paying tax. The population involved in the study is the tax payers of the institution implementing Sunset Policy which there are 150 tax payers. The sampling technique used in the study was Accidental Sampling. It is a technique which the samples used are accidentally met with the researcher, whoever they are if they meet the criteria of the data source are considered as the sample of the research. The data were obtained by questionnaire. The data were analyzed using validity test, reliability test, classic assumption test, multiple linear analysis, t-test, and determination test. The results of these tests show that (1) the t test results in Table 3, obtained t calculate equal to 2,044 with a probability value of 0,043 < 0,05, which means socialization Sunset Policy has a significant influence on the willingness to pay taxes. (2) The t test results in Table 3, obtained t arithmetic amounted to 7,138 with a probability value 0,000 < 0,05, which means understanding Sunset Policy policy has a significant influence on the willingness to pay taxes.Keywords: Sunset policy, socialization, understanding, willingness of paying tax